PERAN DAN TANGGUNG JAWAB KEPALA SEKOLAH DALAM PEMBINAAN GURU PADA SMAN 1 SRENGAT KABUPATEN BLITAR - Achmad Shaffan Waliudin; Prim Masrokan Mutohar; Binti Maunah (Program Studi Manajemen Pendidikan Islam, 2022)
Roles are behaviors that are expected to explain what to do in certain situations, both formally and informally. While responsibility is the obligation to carry out a role/behavior that is intentional or unintentional in a certain way. The principal who is the leader is a teacher who is given additional duties to lead an aducational institution. The principal has a heavy but noble taks. The purpose of this study is to describe the roles and responsibilities of the principal in providing guidance to teachers. The method used is library research, which is looking for reference materials from books, journals and articles related to the title. The result of this study found that the principal in providing guidance to teachers must comply with existing regulations. The principal must understand the science of management, at least he can plan, organize, lead and control his members. Principals also have responsibilities related to coaching staff, especially teachers, so that later teachers can carry out their respective duties and authoritues.